Diplatin, a Novel and Low-Toxicity Anti-Lung Cancer Platinum Complex, Activation of Cell Death in Tumors via a ROS/JNK/p53-Dependent Pathway, and a Low Rate of Acquired Treatment Resistance - Lin, Xixi; Jia, Yongliang; Dong, Xinwei; Shen, Jian; Jin, Yachao; Li, Yanyou; Wang, Fang; Anenberg, Eitan; Zhou, Jiancang; Zhu, Jianping; Chen, Xiaoping; Xie, Qiangmin; et al. (Frontiers in Pharmacology, 2019)
Background: Platinum-based drugs prevail as the main treatment of lung cancer; this is caused by their relative effectiveness despite known side effects, such as neurotoxicity. The risk reward of the treatment and side effects is confronted when dosage is considered and when resistance to treatment develops. Development of new compounds that improve effectiveness and safety profiles addresses this ongoing need in clinical practice. Objectives: The novel water-soluble platinum complex, diplatin, was synthesized, and its antitumor potency and toxicology profile were evaluated in murine xenograft tumor models and in lung cancer cell lines. Methods: The effects of diplatin, cisplatin (DDP), and carboplatin (CBP) on the viability of nine lung tumor cell lines and one normal human lung epithelial cell line were evaluated using the MTT assay. Therapeutic index was calculated as LD50/ED50 to identify and compare the ideal therapeutic windows of the above compounds. Diplatin’s antitumor effects were assessed in lung xenograft tumors of nude mice; molecular mechanisms of therapeutic effects were identified. Results: Diplatin had desirable IC50 compared to CBP in a variety of cultured tumor cells, notably lung tumor cells. In the mouse xenograft lung tumor, diplatin led to a substantially improved therapeutic index when compared to the effects of DDP and CBP. Importantly, diplatin inhibited the growth of DDP-resistant lung tumor cells. Diplatin’s mode of action was characterized to be through cell cycle arrest in the G2/M phase and induction of lung tumor apoptosis via ROS/JNK/p53-mediated pathways. Conclusion: Diplatin was observed to have antitumor effects in mice with both greater potency and safety compared with DDP and CBP. These observations indicate that diplatin is promising as a potential treatment in future clinical applications.